The murine ortholog of Kaufman oculocerebrofacial syndrome gene Ube3b is crucial for the maintenance of the excitatory synapses in the young adult stage. (16th February 2023) - Katsube, Saki; Koganezawa, Noriko; Hanamura, Kenji; Cuthill, Katherine J.; Tarabykin, Victor; Ambrozkiewicz, Mateusz C.; Kawabe, Hiroshi
Highlights: 3D-STED microscopy is a powerful tool to quantify the excitatory synapse numbers. Ube3b loss leads to a global decrease in excitatory synapses in the hippocampal CA1. Ube3b loss leads to a layer-specific decrease in excitatory synapses in the CA2. Ube3b plays a role for the maintenance of synapse numbers in the young adult period. Abstract: Kaufman oculocerebrofacial syndrome (KOS) is an autosomal recessive developmental disorder. Inactivating mutations in UBE3B, an E3 ubiquitin ligase gene are causative for KOS. We have reported that towards postnatal week three, its murine ortholog, Ube3b, acts as a negative regulator of the number of dendritic spines. In this study, we investigated the role of Ube3b at the synapse in the young adult mice. With an improved estimation method, images from the hippocampal CA1 and CA2 regions acquired with 3D Stimulated Emission Depletion (3D-STED) microscopy were used to quantify the excitatory synapse numbers. In the young adult mice, the excitatory synapse density was decreased in brain-specific Ube3b conditional knockout mice as compared to the control. Our results indicate the novel role of Ube3b in the maintenance of synapse numbers in the young adult period.